Inhibitory effect of Scutia buxifolia extracts, fractions, and ursolic acid on Na+, K+-ATPase activity in vitro in membranes purified from rat hearts. (17th February 2016) - Carvalho, Fabiano B.; Boligon, Aline A.; Athayde, Margareth L.; Rubin, Maribel A.; Ferreira, Juliano; Trevisan, Gabriela
Abstract: Ethnopharmacological relevance: Scutia buxifolia is a tree native to South America and is used as a cardiotonic agent; however, this property has not been associated with a clear mechanism or a specific compound. Aim of the study: Given the importance of Na +, K + -ATPase as a drug target in the treatment of heart failure, this study aimed to investigate the possible inhibitory effect of S. buxifolia crude extract and fractions (dichloromethane, ethyl acetate, and butanolic fractions), and identified compounds with effects on the activity of Na +, K + -ATPase in vitro . Materials and methods: First, we characterized the crude extract and fractions by high-performance liquid chromatography, and then monitored their effects on the activity of Na +, K + -ATPase obtained from heart muscle and brain membranes of adult male Wistar rats. Results: We identified gallic acid, chlorogenic acid, caffeic acid, rutin, quercitrin, quercetin, and ursolic acid in S. buxifolia stem bark and leaves; quercitrin and ursolic acid were the main compounds in the ethyl acetate and dichloromethane fractions from leaves and stem bark. The crude extract (3 and 30 mg/ml), and the ethyl acetate and dichloromethane fractions (0.1 and 1 mg/ml) of both the stem bark and leaves inhibited Na +, K + -ATPase activity in heart and brain samples. We found that, of the identified compounds, only ursolic acid (0.1 mg/ml) was able to diminish Na +, K + -ATPase activity in heart and brain samples. Conclusions: These data indicated that the cardiotonic effects of S. buxifolia may be due to the inhibition of Na +, K + -ATPase activity in heart muscle, supporting the popular use of this plant as a treatment for heart failure. Graphical abstract: